Learning with the Mosiulika Mosijagai Method at SMKN 2 Palu, Post-Earthquake in Central Sulawesi - Nurhawaisyah Nurhawaisyah (Jurnal Ad'ministrare, 2021)
Mosiulika Mosijagai is the Kaili Ledo language in the city of Palu, Central Sulawesi Province. Mosiulika means "Say" Mosijagai means "Beware, be careful." In the assessment of skills, the "Mosiulika Mosijagai" method is still used. There are two things that are assessed, namely typing speed and typing accuracy. Of the 30 students tested, there were 19 (63.33%) students who completed, which reached a speed of ≥ 200 EPM as many as 8 (26.67%). In terms of typing accuracy, of the 30 students who were tested, all of them were complete, and those who reached ≥ 99% accuracy were 5 (16.67%). Classical completeness is 100% and classical absorption is 96.13%. The results of the knowledge assessment with the Plickers application are, of the 23 students who took the test with 14 questions that were displayed, there were 11 values ranging from 0 to 50. Only 2 students were able 50% answered questions, there were even students who did not answer correctly or in other words the acquisition was 0%. Classical completeness and classical absorption for typing speed and the realm of knowledge have not been achieved. This is due to constraints due to the lack of learning time in post-natural disasters, while increasing speed requires sufficient time to increase the number of exercises. As for the incompleteness in the realm of knowledge because students as survivors, who have not fully recovered from trauma, still find it difficult to fully concentrate on the subject matter.